Preparation of double-sided roughened solid oxide fuel cell electrolyte membranes by hydrolysis

Through the hydrolysis preparation process, the steps of dry pressing, hydrolysis and one-time high-temperature calcination are used to solve the problem of insufficient controllability of the density and thickness of the electrolyte film in the existing technology, and realize the preparation of an electrolyte film with rough both sides and uniform thickness. Improved battery performance and simplified process flow.

CN118486868BActive Publication Date: 2025-01-24TAIYUAN INST OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410654639.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-05-24
Publication Date
2025-01-24
Estimated Expiration
2044-05-24

AI Technical Summary

Technical Problem

The prior art is difficult to prepare a dense, uniform and rough-sided solid oxide fuel cell electrolyte film, and the traditional dry pressure method requires two high-temperature calcination, which is complicated.

Method used

The hydrolysis preparation process is used to form a double-sided rough solid oxide fuel cell electrolyte film through the steps of dry pressing, hydrolysis and high-temperature calcination. The process includes base material grinding, co-pressing molding, hydrolysis treatment and high-temperature calcination, which simplifies the process flow.

Benefits of technology

It achieves double-sided roughening, ultra-thinness and uniformity of the electrolyte film, improves battery performance, simplifies the process flow, and is suitable for batch preparation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118486868B_ABST
    Figure CN118486868B_ABST
Patent Text Reader

Abstract

The present invention relates to the field of fuel cell technology, and in particular to a hydrolysis method for preparing a double-sided rough solid oxide fuel cell electrolyte film. The hydrolysis method preparation process adopts the steps of dry pressing, hydrolysis, and calcination to prepare a double-sided rough electrolyte film. The overall operation is simple, and only one high-temperature calcination is required to achieve double-sided roughening, ultra-thinning, and uniformity of the solid oxide fuel cell electrolyte film. The double-sided rough solid oxide fuel cell electrolyte film prepared by the method is conducive to closer contact between electrodes and electrolytes, accelerates mass transfer during electrolysis, and thus improves battery performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of fuel cells, and in particular to a hydrolysis method for preparing a double-sided rough solid oxide fuel cell electrolyte film. Background Art

[0002] Solid oxide fuel cell (SOFC) is an electrochemical device that converts chemical energy directly into electrical energy through electrochemical reactions. It has the advantages of high energy conversion rate, strong fuel adaptability and environmental friendliness. Traditional high-temperature SOFC needs to work at around 1000℃. Such a high operating temperature will lead to serious problems such as interface reaction and electrode sintering degradation. Therefore, reducing the operating temperature to medium temperature (500-800℃) is the general trend of SOFC development. The main means to achieve low temperature of SOFC include reducing the ohmic resistance of the battery system by thinning the electrolyte. The most commonly used method for the preparation of electrolyte-supported electrolyte films is dry pressing. This preparation technology has made great progress in the preparation and application of electrolytes, but it still has shortcomings, such as electrolyte film density, controllability of film thickness, uneven grinding leading to anode and cathode peeling, etc., and cannot fully meet the needs of SOFC commercial production.

[0003] Patent No. 2018110564070 of "A Method for Preparing a Zirconium-Based Electrolyte Film for Electrolyte-Supported Solid Oxide Fuel Cell" prepared a zirconium-based electrolyte film for electrolyte-supported solid oxide fuel cells by dry pressing / heating / quenching / calcination. It is a single-sided rough YSZ film. The rough electrolysis is conducive to close contact between the electrode and the electrolyte, accelerating mass transfer during the electrolysis process, thereby improving the battery performance of the YSZ-supported SOFC. This patent has made progress in the ultra-thin and uniform preparation of zirconium-based electrolytes. If the three-layer structure of support layer / YSZ / support layer is prepared and then heated / quenched, the YSZ will easily break due to the curling of the support layers on both sides of the YSZ. Therefore, the dry pressing / heating / quenching / calcination method of this patent is only suitable for preparing a single-sided rough electrolyte film. Summary of the invention

[0004] In order to make up for the shortcomings of the prior art, the present invention provides a hydrolysis method for preparing a double-sided roughened solid oxide fuel cell electrolyte membrane. The operation is simple and only requires one high-temperature calcination to achieve double-sided roughening, ultra-thinning and uniformity of the electrolyte membrane, thus solving the problems existing in the prior art.

[0005] In order to achieve the above-mentioned invention object, the technical solution adopted by the present invention is:

[0006] A hydrolysis method for preparing a double-sided rough solid oxide fuel cell electrolyte membrane comprises the steps of dry pressing, hydrolysis and calcination.

[0007] Furthermore, the specific steps of the above preparation process are as follows:

[0008] (1) Grinding the base material uniformly and pressing it into a sheet using a tablet press to obtain a thin sheet;

[0009] (2) evenly spreading the powder material for preparing the electrolyte film on the surface of the sheet obtained in step (1), and co-pressing the sheet on a tablet press to form a substrate / electrolyte double-layer green body consisting of a substrate layer and an electrolyte layer;

[0010] (3) evenly spreading the substrate material on the electrolyte surface of the substrate / electrolyte double-layer green body obtained in step (2), and co-pressing the green body on a tablet press to form a substrate / electrolyte / substrate three-layer green body;

[0011] (4) placing the substrate / electrolyte / substrate three-layer green body obtained in step (3) on a sieve, and treating the upper and lower substrate layers simultaneously with two small humidifiers to completely dissolve the substrate material in water, thereby making the substrate / electrolyte / substrate three-layer green body into a single electrolyte layer;

[0012] (5) placing the single electrolyte layer obtained in step (4) in an oven to dry the water on its surface, taking it out and placing it on a zirconium oxide plate, and calcining it at high temperature to obtain a dense and uniform double-sided rough solid oxide fuel cell electrolyte membrane.

[0013] Furthermore, the base material in step (1) and step (3) is sodium hydroxide or potassium hydroxide, with a particle size of ≥120 mesh; the molding pressure in step (1) is 80-90 MPa, and the holding time is 40 s.

[0014] Furthermore, in step (2), the particle size of the powder material is ≥80 mesh; the co-pressing pressure is 90-100 MPa, and the holding time is 40 s.

[0015] Furthermore, the powder material in step (2) is a common material such as yttria-stabilized zirconia (YSZ), doped CeO2, doped LaGaO3, etc.; the particle size is ≥100 mesh.

[0016] Furthermore, the co-pressing pressure in step (3) is 100-110 MPa, and the holding time is 1 min.

[0017] Furthermore, in step (4), the humidifier power is 5W, the distance from the substrate layer is 10-15cm, the humidifier treatment time is 3-6min; and the sieve is 60-80 mesh.

[0018] Furthermore, in step (5), the drying temperature is 80-100° C. and the heating time is 30 min-1 h.

[0019] Furthermore, in step (5), the high temperature calcination temperature is 1400° C., the calcination time is 5 h, and the heating rate is 5° C. / min.

[0020] Beneficial effects of the present invention:

[0021] The process of the present invention is simple to operate and is suitable for batch preparation of solid oxide fuel cell electrolyte films with rough double sides and uniform thickness. Compared with the traditional dry pressing method, which requires two high-temperature calcinations for a thicker film to give it a certain hardness, and then uses sandpaper to treat it into a thin film before calcining it, the present invention only requires one high-temperature calcination. Compared with the single-sided rough YSZ film prepared by the dry pressing / heating / quenching / calcination method, the solid oxide fuel cell electrolyte film with rough double sides of the present invention is conducive to closer contact between the electrode and the electrolyte, accelerates mass transfer during the electrolysis process, and thus improves battery performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 The surface roughness of both sides of the electrolyte film measured by a 3D optical profiler in Example 1 of the present invention;

[0023] Figure 2 The surface roughness of both sides of the electrolyte film prepared by the traditional dry pressing method was measured by a 3D optical profilometer;

[0024] Figure 3 The electrochemical performance of the battery prepared by the electrolyte film of Example 1 of the present invention and the electrolyte film-based battery prepared by the conventional dry pressing method under SOFC mode;

[0025] Figure 4 The electrochemical performance of the battery prepared using the electrolyte film of Example 1 of the present invention under the SOEC mode at different temperatures;

[0026] Figure 5 Electrochemical performance of electrolyte thin film-based batteries prepared by traditional dry pressing method at different temperatures in SOEC mode;

[0027] Figure 6 The electrochemical performance of a battery prepared by using the electrolyte film of Example 1 of the present invention and an electrolyte film-based battery prepared by a conventional dry pressing method at 850° C. in SOEC mode;

[0028] in, Figure 3-Figure 6 The "hydrolysis, traditional" indicated in the figure correspond to the solid oxide fuel cell electrolyte membrane (or a battery made therefrom) of Example 1 of the present invention and the electrolyte membrane (or electrolyte membrane-based battery) prepared by the traditional dry pressing method, respectively. DETAILED DESCRIPTION

[0029] In order to clearly illustrate the technical features of this solution, the present invention is described in detail below through specific implementation methods and in conjunction with the accompanying drawings. The scope of the present invention is not limited to the following embodiments. Professionals in the field can understand that various changes and modifications can be made to the present invention without departing from the spirit and scope of the present invention.

[0030] The instruments, reagents, materials, etc. involved in the following embodiments, unless otherwise specified, are all conventional instruments, reagents, materials, etc. in the prior art and can be obtained through regular commercial channels. The experimental methods, detection methods, etc. involved in the following embodiments, unless otherwise specified, are all conventional experimental methods, detection methods, etc. in the prior art.

[0031] Example 1

[0032] A hydrolysis method for preparing a double-sided rough solid oxide fuel cell electrolyte membrane includes the steps of dry pressing-hydrolysis-calcination. Sodium hydroxide is used as the base material and YSZ (8% yttrium-stabilized zirconium dioxide) is used as the electrolyte to prepare the YSZ electrolyte membrane. The specific operation steps are as follows:

[0033] (1) Grind sodium hydroxide evenly, weigh 0.15 g of powder, and press it into a sheet with a thickness of about 180 μm using a tablet press with a diameter of 15 mm and a pressure of 80 MPa for 40 seconds;

[0034] (2) 0.2 g of electrolyte YSZ powder was evenly spread on the surface of the thin slice in step (1), and co-pressed at a pressure of 90 MPa for 40 s to form a substrate / electrolyte double-layer green body;

[0035] (3) evenly spreading 0.1 g of sodium hydroxide material on the electrolyte surface of the substrate / electrolyte double-layer green body obtained in step (2), and co-pressing the green body on a tablet press at a pressure of 100 MPa for 1 min to form a substrate / electrolyte / substrate three-layer green body;

[0036] (4) placing the substrate / electrolyte / substrate three-layer green body on an inclined (inclination angle of 30 degrees to the horizontal plane) 60-mesh sieve, and using two 5W small humidifiers to treat the upper and lower substrate layers simultaneously, so that the substrate material sodium hydroxide is completely dissolved, thereby making the substrate / electrolyte / substrate three-layer green body into a single electrolyte YSZ layer;

[0037] (5) Place the layer in an oven and dry it at 100°C for 40 min to dry the water on the surface of the YSZ electrolyte layer. Take out the electrolyte layer and place it on a zirconia plate. Sinter the layer at 1400°C for 5 h at a heating rate of 5°C / min to obtain a double-sided rough, dense and uniform electrolyte-supported solid oxide fuel cell electrolyte membrane.

[0038] Gold spraying was performed on both sides of the solid oxide fuel cell electrolyte membrane prepared above, and the surface roughness was tested using a 3D optical profiler. Figure 1 As shown in FIG. 1 , the root mean square roughness of the two sides of the solid oxide fuel cell electrolyte membrane prepared above was measured to be 3.443 and 3.576 μm respectively. In comparison, 0.2 g of YSZ powder was prepared by conventional direct dry pressing to obtain an electrolyte membrane, and the root mean square roughness of the two sides was 0.325 and 0.548 μm respectively. Figure 2 shown.

[0039] Example 2

[0040] A hydrolysis method for preparing a double-sided rough solid oxide fuel cell electrolyte membrane, using potassium hydroxide as the base material and YSZ (8% yttrium-stabilized zirconium dioxide) as the electrolyte, to prepare a YSZ electrolyte membrane. The specific steps are as follows:

[0041] (1) Grind potassium hydroxide evenly, weigh 0.15 g of the powder, and press it into a sheet with a thickness of about 190 μm using a tablet press with a diameter of 15 mm and a pressure of 80 MPa for 40 seconds;

[0042] (2) 0.2 g of electrolyte YSZ powder was evenly spread on the surface of the thin slice in step (1), and the pressure was maintained at 100 MPa for 40 seconds, and co-pressed to form a substrate / electrolyte double-layer green body;

[0043] (3) evenly spreading 0.1 g of potassium hydroxide material on the electrolyte surface of the substrate / electrolyte double-layer green body obtained in step (2), and co-pressing the green body under a pressure of 110 MPa for 1 min on a tablet press to form a substrate / electrolyte / substrate three-layer green body;

[0044] (4) placing the substrate / electrolyte / substrate three-layer green body on an inclined (inclination angle of 30 degrees to the horizontal plane) 70-mesh sieve, and using two 5W small humidifiers to treat the upper and lower substrate layers simultaneously, so that the substrate material sodium hydroxide is completely dissolved, thereby making the substrate / electrolyte / substrate three-layer green body into a single electrolyte YSZ layer;

[0045] (5) Place the layer in an oven and dry it at 80°C for 1 hour to dry the water on the surface of the YSZ electrolyte layer. Take out the electrolyte layer and place it on a zirconia plate. Sinter the layer at 1400°C for 5 hours at a heating rate of 5°C / min to obtain a double-sided rough, dense and uniform electrolyte-supported solid oxide fuel cell electrolyte membrane.

[0046] Example 3

[0047] A YSZ electrolyte film prepared by conventional direct dry pressing of 0.2 g YSZ powder was sprayed with cathode and anode electrode layers on both sides to prepare a battery for performance comparison with a battery made of a solid oxide fuel cell electrolyte film prepared by hydrolysis in Example 1.

[0048] The electrochemical performance of the battery was tested under H2 atmosphere at 850°C using an electrochemical workstation. Figure 3 As shown, the current-voltage (power) discharge curve is obtained. It can be seen that under the same conditions, compared with the battery prepared by the traditional dry pressing method, the maximum power density and maximum current density of the battery prepared by the improved solid oxide fuel cell electrolyte membrane in Example 1 of the present invention are significantly improved.

[0049] The electrochemical workstation was used to test the battery's pure CO2 electrolysis performance at 750°C, 800°C, and 850°C, and the current-voltage discharge curves were obtained. Figure 4 , 5 As shown, it can be seen that at the same voltage, as the temperature increases, its CO2 electrolysis performance also improves. Compared with traditional batteries, the water-removal improved battery made of the solid oxide fuel cell electrolyte membrane in Example 1 of the present invention has significantly better CO2 electrolysis performance. In addition, compared with traditional batteries, at the same temperature, the water-removal improved battery made of the solid oxide fuel cell electrolyte membrane in Example 1 of the present invention has higher CO2 electrolysis performance. Figure 6 As shown in the figure, the current density of the conventional battery for CO2 electrolysis at 850℃ and 1.6V is 1.31A cm -2 Under the same conditions, the current density of the hydrolysis improved cell made of the solid oxide fuel cell electrolyte membrane of Example 1 of the present invention was increased to 1.65 A cm -2 , an increase of 26%.

[0050] The above specific implementation manner cannot be used as a limitation on the protection scope of the present invention. For those skilled in the art, any substitution, improvement or change made to the implementation manner of the present invention falls within the protection scope of the present invention.

[0051] The matters not described in detail in the present invention are all known technologies to those skilled in the art.

Claims

1. A hydrolysis method for preparing a double-sided rough solid oxide fuel cell electrolyte membrane, characterized in that: The method comprises the steps of dry pressing, hydrolysis and calcination; the specific steps are as follows: (1) Grinding the base material evenly and molding it into sheets to obtain thin sheets; (2) evenly spreading the powder material for preparing the electrolyte film on the surface of the sheet obtained in step (1), and co-pressing to form a substrate / electrolyte double-layer green body consisting of a substrate layer and an electrolyte layer; (3) evenly spreading the substrate material on the electrolyte surface of the substrate / electrolyte double-layer green body obtained in step (2), and co-pressing to form a substrate / electrolyte / substrate three-layer green body; (4) placing the substrate / electrolyte / substrate three-layer green body obtained in step (3) on a sieve, and treating the upper and lower substrate layers simultaneously with a humidifier to completely hydrolyze the substrate material, thereby forming a single electrolyte layer in the substrate / electrolyte / substrate three-layer green body; (5) drying the water on the surface of the single electrolyte layer obtained in step (4), taking it out and placing it on a zirconia plate, and calcining it at high temperature to obtain a dense and uniform double-sided rough solid oxide fuel cell electrolyte membrane; The base material in step (1) and step (3) is sodium hydroxide or potassium hydroxide.

2. The hydrolysis method for preparing a double-sided rough solid oxide fuel cell electrolyte membrane according to claim 1, characterized in that: In step (1) and step (3), the particle size of the base material is ≥120 mesh; in step (1), the molding pressure is 80-90 MPa, and the holding time is 40 s.

3. The hydrolysis method for preparing a double-sided rough solid oxide fuel cell electrolyte membrane according to claim 1, characterized in that: Step (2) The particle size of the powder material is ≥80 mesh; the co-pressing pressure is 90-100 MPa, and the holding time is 40 s.

4. The hydrolysis method for preparing a double-sided rough solid oxide fuel cell electrolyte membrane according to claim 1 or 3, characterized in that: The powder material of step (2) is yttria-stabilized zirconia, doped CeO2 or doped LaGaO3; the particle size is ≥100 mesh.

5. The hydrolysis method for preparing a double-sided rough solid oxide fuel cell electrolyte membrane according to claim 1, characterized in that: The co-pressing pressure in step (3) is 100-110 MPa, and the holding time is 1 min.

6. The hydrolysis method for preparing a double-sided rough solid oxide fuel cell electrolyte membrane according to claim 1, characterized in that: Step (4) The humidifier power is 5W, the distance from the substrate layer is 10-15cm, and the humidifier treatment time is 3-6min; the sieve is 60-80 mesh.

7. The hydrolysis method for preparing a double-sided rough solid oxide fuel cell electrolyte membrane according to claim 1, characterized in that: The drying temperature in step (5) is 80-100° C. and the heating time is 30 min-1 h.

8. The hydrolysis method for preparing a double-sided rough solid oxide fuel cell electrolyte membrane according to claim 1, characterized in that: The high-temperature calcination temperature of step (5) is 1400°C, the calcination time is 5h, and the heating rate is 5°C / min.